Age, Growth and Reproduction of Coryphaena hippurus (Linnaeus, 1758) in Maltese Waters, Central Mediterranean - GATT, M.; DIMECH, M.; SCHEMBRI, P. J. (Mediterranean Marine Science, 2015)
Age, growth and reproduction of the dolphinfish Coryphaena hippurus Linnaeus, 1758 collected from the Central Mediterranean in the period 2004-2010 by the traditional Maltese fish aggregating devices (FAD) and surface longline fisheries were studied. The a and b parameters of the length-weight relationship for fish 11-142 cm fork length (FL) (n = 4042) were determined as a = 0.018 and 0.022 with b = 2.85 and 2.79, for males and females respectively. The counting of annual increments from dorsal spines of >65 cm FL dolphinfish at X25 magnification (n = 47) permitting an age reading resolution in years , and the counting of daily increments from sagittal otoliths of <65 cm FL dolphinfish at X400 magnification (n = 583) permitting an age reading resolution in days, were estimated; the von Bertalanffy growth model applied to these fish gave the following parameters: L∞ = 107.8 cm FL and 120.2 cm FL, and K = 1.9 yr-1 and 1.56 yr-1, for males and females respectively. The maximum age observed was 2 years. Size at 50% maturity for fish 10-131 cm FL (n = 1376) was 58.9 cm FL and 62.5 cm FL for males and females, respectively. The sex ratio for the fish sampled from the FAD fishery (10.5-131 cm FL) was 1:1.54 (M:F) and for dolphinfish sampled from the surface longline fishery (91-130 cm FL) was 1:0.76 (M:F). Back-calculated hatch dates from age-0 dolphinfish (n = 518) suggested that spawning occurs from June to September with the highest levels in June. This study is the first to use dorsal spines to determine the age of adult dolphinfish.